Aerobic training in patients with anoctamin 5 myopathy and hyperckemia. Issue 1 (5th May 2014) - Vissing, Christoffer R.; Preisler, Nicolai; Husu, Edith; Prahm, Kira P.; Vissing, John
ABSTRACT Introduction: Anoctamin 5 deficiency has recently been defined to cause limb‐girdle muscular dystrophy type 2L (LGMD2L) with pronounced hyperCKemia. No treatment interventions have been made so far in this condition. Methods: In 6 patients with LGMD2L, we studied the effect of home‐based, pulse‐watch monitored, moderate‐intensity exercise on a cycle ergometer for 30 minutes, 3 times weekly, for 10 weeks. Plasma creatine kinase (CK) was assessed before, during, and after the program as a marker of muscle damage. Primary outcome measures were maximum oxygen uptake (VO2max) and time in the 5‐repetitions‐sit‐to‐stand test (FRSTST). Results: Training resulted in improvements in VO2max (27 ± 7%; P = 0.0001) and FRSTST time (35 ± 12%; P = 0.007). Improvements in physiologic and functional muscle testing were accompanied by stable CK levels and no reports of adverse effects. Conclusions: These findings suggest that supervised aerobic exercise training is safe and effective in improving oxidative capacity and muscle function in patients with anoctamin 5 deficiency. Muscle Nerve50: 119–123, 2014